Hubungan Kedekatan Personal ARMY terhadap BTS dengan Perilaku Aktivisme Sosial Online - Pitopili, Innayah; Pratamawaty, Benazir Bona (Jurnal Pustaka Komunikasi, 2024)
The feeling of personal closeness between fans and their idols is the basis of the parasocial relationship that is often experienced by K-Pop fans, including ARMY and BTS. This parasocial relationship can make fans do anything for their idols, one of which is to carry out acts of social activism on behalf of their fandom and idols. Social activism is a positive behavior that is an action taken with the aim of bringing about change in society. The purpose of this study is to examine whether there is a relationship between ARMY's personal closeness to BTS and ARMY's online social activism behavior. This research was conducted through quantitative methods with sampling techniques using G*power. In the calculation stage, the Statistical Test was carried out with the structural equation model test. The results of statistical analysis using the help of JASP and SMARTPLS, state that the hypothesis that researchers build is accepted. From this it can be concluded that in line with previous research that the personal closeness between ARMY and BTS can be the basis for the behavior of fans, one of which is social activism because the two variables have a significant relationship.